2017
DOI: 10.1007/s12032-017-1033-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in situ hybridization as prognostic predictor of tumor recurrence during treatment with Bacillus Calmette–Guérin therapy for intermediate- and high-risk non-muscle-invasive bladder cancer

Abstract: A significant number of patients with intermediate- or high-risk bladder cancer treated with intravesical Bacillus Calmette–Guérin (BCG) immunotherapy are non-responders to this treatment. Since we cannot predict in which patients BCG therapy will fail, markers for responders are needed. UroVysion® is a multitarget fluorescence in situ hybridization (FISH) test for bladder cancer detection. The aim of this study was to evaluate whether FISH can be used to early identify recurrence during treatment with BCG. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…Among these records, 4 studies were reviews, and 1 study was a duplicate. Finally, data from 6 studies [ 15 20 ] were synthesized in this diagnostic meta-analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these records, 4 studies were reviews, and 1 study was a duplicate. Finally, data from 6 studies [ 15 20 ] were synthesized in this diagnostic meta-analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The difference was hypothesized that patients did not have benefitted from BCG induction therapy yet at baseline time. [ 20 , 24 ] And multiple studies [ 25 27 ] have reported the persistence of genetically aberrant cells after TURBT, which necessitated adjuvant therapy but not eventually progress to recurrence. Meanwhile, as the median time to recurrence after BCG reported was reported to be 26 months, [ 28 ] the median follow-up time of 16 to 23.4 months in this pooled study may not be long enough to detect all recurrences, which may also contribute to the false-positive rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, these are general factors for poor cancer prognosis instead of predictive biomarkers. Urine cell genomic alterations detected by fluorescence in situ hybridisation during BCG treatment, although with low sensitivity , increased several fold cancer recurrence and progression risk . Next generation sequencing (NGS) is infrequently applied for BCG response prediction studies.…”
Section: Biomarkers To Predict the Response Of Immune Therapiesmentioning
confidence: 99%
“…The UroVysion test is a multicolor fluorescence in situ hybridization (FISH) assay designed to detect aneuploidy of chromosomes 3, 7, or 17, and/or the loss of the 9p21 locus [ 28 ]. A series of recent reports showed that utilization of FISH-based assay may be used as an additional tool for subclassification of patients or determining a treatment option [ 29 30 31 32 ].…”
Section: Application To Bladder Cancer Studymentioning
confidence: 99%